Altered pharmacodynamics and pharmacokinetics of cisatracurium in patients with severe mitral valve regurgitation during anaesthetic induction period - Liu, Jiayi (Br J Clin Pharmacol, 2016)
AIM: The aim of the current study was to characterize the pharmacokinetics (PK) and pharmacodynamics (PD) of cisatracurium in patients with severe mitral valve regurgitation (MR) during the anaesthetic induction period. METHODS: Thirty patients in the clinical trial were divided into two groups: the MR group (n = 15) and the control group (n = 15). Arterial blood samples were obtained before (time 0) and at 1, 2, 4, 6, 8, 10, 15 and 20 min after intravenous injection of 0.15 mg kg(−1) cisatracurium. The degree of neuromuscular block was measured by train of four (TOF) testing. The concentration of cisatracurium in the plasma was determined by high‐performance liquid chromatography. A conventional two‐compartment model and integrated PK/PD model were applied to PK and PD data analysis, respectively. RESULTS: The results of PK model fitting demonstrated that severe MR reduced the distribution rate of cisatracurium from the central to peripheral compartment, resulting in a higher concentration of the drug in the plasma. The time to the maximal neuromuscular blocking effect of cisatracurium was delayed in the MR group (2.08 min in the control group vs. 4.12 min in the MR group). The PK/PD model indicated that the distribution rate of cisatracurium from the blood to the effect compartment was decreased in the MR group. CONCLUSIONS: The present study suggested that the PK and PD of cisatracurium were significantly altered in patients with severe MR. The study has the potential to improve the safety of anaesthetic induction in patients with severe MR through accurate prediction of the PD responses of cisatracurium using the established PK/PD model.